Pengaruh Kepuasan Kerja dan Lingkungan Kerja Terhadap Organizational Citizenship Behaviour (OCB) Melalui Loyalitas Karyawan sebagai Variabel Mediasi (Suatu Kajian Studi Literatur Manajemen Sumberdaya Manusia) - A. Sara, Muslikhan; Sia Niha, Simon; A. Manafe, Henny (Jurnal Ilmu Manajemen Terapan, 2023)
This review intends to be able to determine hypotheses that are able to influence each variable in order to provide benefits for further reviews. The results obtained in this description are as follows: 1) Job satisfaction has a positive and meaningful impact on employee loyalty; 2) The work environment has a positive and significant impact on employee loyalty; 3) Job satisfaction has a positive and significant influence on organizational citizenship behavior (OCB); 4). The work environment has a positive and meaningful impact on organizational citizenship behavior (OCB); 5). Employee loyalty has a positive and crucial effect on organizational citizenship behavior (OCB) 6). Employee loyalty can mediate job satisfaction which influences organizational citizenship behavior (OCB). 7) Loyalty to employees can mediate the work environment that influences organizational citizenship behavior (OCB); 8) job satisfaction and work environment simultaneously have a positive or significant influence on organizational citizenship behavior (OCB).